Penggunaan Zeolit Sebagai Media Penyaring Pada Pengolahan Air LimbahDomestik - Yanto, Yanto (Jenderal Soedirman University, 2011)
Sand filter is frequentlyused to treat contaminated water. Channel filter system is a modification of sand filter where the channel is shaped thus the land requirement could be minimized, water is flowed horizontallyfrom intial tank to finaltank through sand filter. Employing the channel filter to treat domestic wastewateris capable of reducing E. Coli up to 98.14%, increasing DO up to 27% and decreasing BOD5 up to 27%. Unfortunately, the final content of E.Coli after treatment process completed is still unacceptable for drinking water. Several options are available to improve the performance of the channel filter system. One of the promising alternativesis modifying the filter medium. Zeolite is natural material that has been utilized to improvewater quality based on several parameters such as Fe, Mn, organic materials, CO and others. Application of zeolite to diminish E. Coli is a challenge. This paper will investigate the effectiveness of zeolite to lower E. Coli contained in domestic wastewater . Zeolite was added to sand filter where thefraction of zeolite is about 5%. Two kind of zeolite-sand combination was implemented that is arranged and mixed zeolite-sand. Wastewater containing E.Coli was then put in the initial tank. Through the hole createdin the tank, wastewater then flowed passing through the combined zeolite-sand filter and accumulated in the final tank. Both E. Coli from initial and final tank was measured to compute treatment efficiency. The result showsE. Coli decreases up to99.99%, BOD5and DO decrease more than 71% and 66% respectively. It can be concluded that 5% addition ofzeolite is able to improve treatment efficiency ofsand filter.